Morphological changes of the interventricular septum rupture in differentperiods after the rupture - V. I. Ursulenko; A. V. Rudenko; N. L. Rudenko; V. P. Zakharova (Ukrainian Journal of Cardiovascular Surgery, 2016)
Postinfarction ventricular septal rupture is mechanically threatening complication is myocardial infarction resulting from damage to the partition, resulting in brittle fracture of necrotic myocardial tissue, without surgical intervention which quickly leads to progressive development of congestive heart failure and the death of patients. Knowledge of all morphological changes in the myocardium allows to create optimum surgical tactics and avoid complications in the postoperative period.